2006
DOI: 10.1128/mcb.00305-06
|View full text |Cite
|
Sign up to set email alerts
|

GIPC Is Recruited by APPL to Peripheral TrkA Endosomes and Regulates TrkA Trafficking and Signaling

Abstract: GIPC is a PDZ protein located on peripheral endosomes that binds to the juxtamembrane region of the TrkA nerve growth factor (NGF) receptor and has been implicated in NGF signaling. We establish here that endogenous GIPC binds to the C terminus of APPL, a Rab5 binding protein, which is a marker for signaling endosomes. When PC12(615) cells are treated with either NGF or antibody agonists to activate TrkA, GIPC and APPL translocate from the cytoplasm and bind to incoming, endocytic vesicles carrying TrkA concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
150
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(156 citation statements)
references
References 49 publications
(62 reference statements)
6
150
0
Order By: Relevance
“…APPL has also been correlated with GIPC/synectin in the control of TrkA trafficking and signaling (58), and GIPC is another important protein involved in VEGFR-2 trafficking (59). We also knocked down GIPC in HUVECs and found that the VEGFR-2 mRNA level was unmodified (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…APPL has also been correlated with GIPC/synectin in the control of TrkA trafficking and signaling (58), and GIPC is another important protein involved in VEGFR-2 trafficking (59). We also knocked down GIPC in HUVECs and found that the VEGFR-2 mRNA level was unmodified (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic disruption of both GIPC and megalin in mice yields low molecular weight proteinuria, a defect also seen in Lowe Syndrome and Dent Disease [20,21]. Additionally, APPL1 could link OCRL to TrkA, which could help explain the cognitive manifestations of Lowe Syndrome [11,22,23]. Dual color immunofluorescence of cells expressing Myc-APPL1 (red) and wild type HA-OCRL or HA-OCRL with patient mutations (green).…”
Section: Discussionmentioning
confidence: 99%
“…GIPC interacts with the juxtamembrane region of TrkA (Liu et al 2001). Characterization of this interaction demonstrated that knock-down of GIPC results in the slowed internalization and retrograde trafficking of TrkA, as well as in the inhibition of NGF-mediated Akt and ERK phosphorylation (Varsano et al 2006). The Xenopus homolog of mammalian GIPC, xGIPC, or Kermit 2, also has been implicated in IGF-IR signaling by directly interacting with the IGF-IR and promoting IGF-I stimulated MAPK signaling and Xenopus oocyte maturation (Booth et al 2002).…”
Section: Receptor Interacting Proteinsmentioning
confidence: 99%